Penerapan Pembelajaran Berbasis Masalah Berbantu Wordwall pada Materi Kesebangunan Kelas VII MTs. Maftahul Ulum - Mufidah, Tuhfatul; Sari, Ayu Silvi Lisvian; Kristiani (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematics learning in schools often faces challenges such as student noise during explanations, low learning outcomes, and limited student engagement in the learning process. To address these issues, a student-centered learning model supported by digital technology is needed. This study employed instruments including student activity observation sheets, teacher activity observation sheets, and student learning achievement tests. Data collection techniques in this research involved observation and student learning achievement tests. The data analysis technique was conducted by compiling data from all instruments. The aim of this study was to describe the implementation of the problem-based learning model assisted by the Wordwall interactive media on the topic of similarity in Grade VII at MTs. Maftahul Ulum. The method used was Classroom Action Research (CAR). The results showed that student activity obtained an average score of 3.45 in the active category, while teacher activity obtained an average score of 3.58 in the very active category; both met the success criteria. In the student learning achievement test, the highest score achieved was 98, the lowest score was 55, and the average score was 83.05 with a mastery level of 77.77% (14 students passed out of 18). Based on these results, it can be concluded that the implementation of problem-based learning assisted by Wordwall in the topic of similarity, particularly the subtopic of the relationship between angles and similarity in Grade VII at MTs. Maftahul Ulum Karangsono, has met the success criteria